THE REDUCED NORMATIVE PROGRAMMING OF ENVIRONMENTAL PROTECTION LAWS IN BRAZIL AND THEIR POORLY ORGANIZED METHODICALLY INTERPRETATION - J. Krell, Andreas (Revista Brasileira de Direito Animal, 2020)
The article addresses an issue poorly discussed by the Brazilian Environmental Law, namely: its low legislation normative programming level. An analysis of legal texts about fields such as licensing shows that formal laws have only few rules that drive clear decisions about conflicts due to conflicting interests. Rules that open wide discretionary room for the interpretation/application of managerial and judicial bureaus often prevail. A documental, bibliographic and jurisprudential research will show that lack of minimum hermeneutical reasoning standard in doctrine and jurisprudence, whose content mostly depends on the individual convictions of public agents judging the claim, causes low decision predictability. The act of weighing the principles follows a rational argumentation line and impairs juridical safety. It would be useful and viable to revalorize classical elements of Law interpretation in combination with modern constitutional hermeneutical techniques in order to replace a complex “environmental hermeneutics”.